1995
DOI: 10.1111/1523-1747.ep12606231
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Collagenase Is Expressed by Keratinocytes That Are Actively Involved in Reepithelialization in Blistering Skin Diseases

Abstract: Migrating keratinocytes actively involved in reepithelialization in dermal wounds acquire a collagenolytic phenotype upon contact with the dermal matrix. To determine whether this phenotype is associated with repair in other forms of wounds, we assessed collagenase expression in 50 specimens representing a variety of blistering skin diseases, including subtypes of epidermolysis bullosa, porphyria cutanea tarda, bullous pemphigoid, pemphigus, transient acantholytic dermatosis, and suction blisters. Distinct fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 32 publications
4
52
0
1
Order By: Relevance
“…One, as we (3,4) and others reported (6), immunostaining for type IV collagen or laminin showed that collagenase-1-positive keratinocytes are not in contact with a basement membrane but rather are moving over the dermal or wound bed matrix. Two, collagenase-1 is not expressed by basal keratinocytes in nonulcerative pyogenic granuloma or in blisters, such as bullous pemphigoid, which separate above basement membrane, but this MMP is expressed by migrating keratinocytes in blisters that form below the basement membrane, such as in recessive dystrophic epidermolysis bullosa (3,4). Three, in acute wounds (3,6) and in cultured skin equivalent models (20), collagenase-1 expression ceases once re-epithelialization is completed and a basement membrane has reformed.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…One, as we (3,4) and others reported (6), immunostaining for type IV collagen or laminin showed that collagenase-1-positive keratinocytes are not in contact with a basement membrane but rather are moving over the dermal or wound bed matrix. Two, collagenase-1 is not expressed by basal keratinocytes in nonulcerative pyogenic granuloma or in blisters, such as bullous pemphigoid, which separate above basement membrane, but this MMP is expressed by migrating keratinocytes in blisters that form below the basement membrane, such as in recessive dystrophic epidermolysis bullosa (3,4). Three, in acute wounds (3,6) and in cultured skin equivalent models (20), collagenase-1 expression ceases once re-epithelialization is completed and a basement membrane has reformed.…”
Section: Discussionsupporting
confidence: 57%
“…Conversely, keratinocyte migration in and of itself does not induce collagenase-1 expression. For example, collagenase-1 is not expressed by keratinocytes involved in re-epithelialization of lesions with an intact basement membrane, such as suction blisters or early bullous pemphigoid blisters (3,4). In addition, collagenase-1 is not expressed by cultured keratinocytes on gelatin, even though these cells can migrate on this substrate (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Skin healing is dependent upon several processes that comprise inflammation, protein synthesis, matrix deposition, migration and subsequent proliferation of keratinocytes (Kanzler et al, 1986;Clark, 1993). Keratinocytes are known to secrete numerous proteins that include proteolytic enzymes such as matrix metalloproteinases (Stamenkovic, 2003), interstitial collagenase (Saarialho-Kere et al, 1995) and cathepsin B (Buth et al, 2004). It is presumed that during the wound healing process, these proteolytic enzymes play a role in motility of keratinocytes by remodeling the extracellular matrix for migration of keratinocytes to peripheral layers of the epidermis.…”
Section: Introductionmentioning
confidence: 99%